Histological study of the modified metatarsal gland in the alpaca (Vicugna pacos) - Pacheco, Joel Iván (2022)
Alopecic areas have been described in the lateral and medial area of the metatarsus of South American camelids, and have been called "metatarsal glands", analogous to those present in cervids. In this study, tissue samples were collected from the metatarsal region of 8 specimens (6 adult alpacas and two foetuses [5 and 8 months]) in the slaughterhouse of Sicuani, Cusco (Peru), and were fixed in 10% buffered formalin and processed by the standard histological technique. Six samples were stained with Hematoxylin-Eosin, PAS and Golden Masson's Trichrome, and were subsequently evaluated by brightfield microscopy, and two samples of adult alpacas were processed by freezing cutting with a cryostat and subsequent differential lipid staining with Nile red and nuclear contrast with Hoecht 33342 and evaluated by fluorescence microscopy. A high epidermal tissue was observed, made up of main cells of the lipokeratinocyte type, with the presence of vacuoles with lipid content (Nile red). The epidermis presents columnar projections that approach the epidermal surface, serving as supportive and nutritious tissue as it contains capillaries and collagen fibres; the basal lamina of the epidermis has papillae that give rise to these projections. In the foetal samples the same structure is observed, but with less height, in addition to presenting the epidermal membrane described in camelid foetuses. It is concluded that these structures are not compatible with glandular tissue as they do not present glandular acini or secretory ducts, being determined as a modified glandular epithelium with sebaceous-lipid secretion.